Pengaruh Budaya Organiasasi, Pelatihan Kerja, dan Disiplin Kerja Terhadap Kinerja Pegawai Biro Kepegawaian di Badan Narkotika Nasional - Della Regita Putri; Ika Suhartanti Darmo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of organizational culture, job training and work discipline on the performance of staffing and employee bureau organizations in the National Narcotics Agency. This research uses quantitative methods by conducting surveys and testing to all employees in the company. The test results show that organizational culture variables have a significant effect on employee performance variables, training variables do not have a significant effect on employee performance variables, and work discipline variables have a significant effect on employee performance. This research was assisted by IBM SPSS 25 as a data processing tool. The number of respondents in this study were 54 people. Based on the tm test organizational culture variables have t arithmetic ≥ t table = 2.180> 2.00856, work training variables have t arithmetic ≥ t table = -1.284 <2.00856, and work discipline variables have t arithmetic ≥ t table = -1.284 < 2.00856. This shows that organizational culture and work discipline variables have a significant effect, while work training variables have no significant effect.